Successful investment strategy - Craig, Malcolm (Cambridge, England : Woodhead-Faulkner, 1989)
The book is a guide for both private and professional investors written from Malcolm Craig's long experience of banking, finance and investment field. This book describes the theory and shows how to put it into practice.
Includes index.
osc 10/05/2018
Loans
Keywords: Investments; Investments